The European Parliament and the Reign of Activists and Experts - Reydams, Luc (Review of European and Comparative Law, 2025)
The article demonstrates the influence of activist non-governmental organizations (NGOs) at the European Parliament (EP) through the case of a suppressed study on universal criminal jurisdiction. It recounts how a report commissioned, approved, and published by the EP was withdrawn after pressure from an NGO with ties to EU grantmaking and policymaking circles. Through an institutional and political analysis, the study reveals how expert discourse, funding mechanisms, and ideological alliances promote international criminal justice. The article challenges the assumed neutrality of academic expertise in supranational institutions and raises broader concerns about transparency and symbolic use of law.